On uniform attractors for non-autonomous p-Laplacian equation with a dynamic boundary condition - Yang, Lu; Yang, Meihua; Wu, Jie (Topological Methods in Nonlinear Analysis, 2013)
In this paper, we consider the non-autonomous p-Laplacian equation with a dynamic boundary condition. The existence and structure of a compact uniform attractor in W^1,p(Ω)× W^1-1/p,p(Γ) are established for the case of time-dependent internal force h(t). While the nonlinearity f and the boundary nonlinearity g are dissipative for large values without restriction on the growth order of the polynomial.